Combinational approaches to optimize narrative writing skills, visual literacy and creativity: local history tales through pictures and comics - Mary, Kampouropoulou; Evangelia, Moula (Advances in Social Sciences Research Journal, 2015)
In this paper we describe our effort to combine various techniques and methods in order to enhance students’ writing skills and at the same time to develop their visual literacy and to encourage their creativity. Taken into account that the established language- based literacy pedagogy and the traditional methodology proves itself on the one hand, ineffective and on the other, inadequate, under the current cultural circumstances, with the dominant presence of multimodality, we propose a lesson plan, which is based on a multi- dimensional concept of literacy, including creativity. The main underpinning theories are: interdisciplinary approach, process writing, writing across the curriculum, iconology, grammar of visual design and dual coding approach. With the emphasis shifted from genre as product to genre as process, students play with the technologies of genre, text, grammar and pictures in a creative fashion and even more they create their own visual narratives. In addition, the starting point of our teaching was a theme from local history (medieval times in Rhodes) which triggered their interest and helped them investigate the historical era and also acquire knowledge about it.